ANALYSIS OF THE INFLUENCE OF STUDENTS' KNOWLEDGE OF BANK INTEREST AND SHARIA ACCOUNTING ON INTEREST IN PURCHASING SHARIA PRODUCTS - Puspitasari, Ratih; Muhammad Irsyad Elfin Mujtaba; Teguh Prakoso; Upik Djaniar; Andri Yunus (Bajang Institute, 2024)
The aim of this research is to analyze the influence of students' knowledge of bank interest and sharia accounting on interest in purchasing sharia products. This research is categorized as partly quantitative research, the type of which is a correlational method. Population in this study were students from Private Universities in Indonesia. Sampling technique that can be used in this research is purposive sampling. Sample studied was 100 respondents. This research uses multiple linear regression analysis to answer the problem formulation and temporary assumptions. The research results show that students' knowledge of bank interest has a positive and significant influence on interest in purchasing sharia products. Sharia accounting has a positive and significant influence on interest in purchasing sharia products.